Il crowdfunding per progetti culturali - D'Amato, Francesco (Mediascapes journal, 2017)
The aim of the article is to offer a critical review of the scientific literature regarding the use of crowdfunding for the financing of cultural projects. More specifically, it will examine what has been noticed about the various interpretations and uses of crowdfunding, the relationship between promoters and backers, the opportunities and the criticalities it presents to different types of promoters and different types of projects, as well as about the factors that affect such aspects. The article is subdivided into three sections The first section considers the motivations of different kind of promoters, the different rhetoric they use to promote the campaigns, the skills and resources need to effectively design and manage the campaigns. In this regard, research shows the extreme relevance of the promoter's social capital for the campaign results. The second section is therefore devoted to the analysis of the different types of social capital mobilized in crowdfunding, of the mobilization strategies implemented by the promoters, of the factors that influence such mobilization and - more generally - that affect the composition of the backers networks. The analysis of these dynamics directs the attention to the skill and resources needed by promoters, to their relationship with funders, and to the ways in which the latter are involved and invited to participate in the projects, besides its funding. The last section is therefore devoted to the critical analysis of crowdfunding, which highlights both the limits of the actual participation of funders, and hence the distance of the prevailing forms of crowdfunding from potentially more innovative models, as well as the asymmetries between different kind of promoters, that is different possibilities to maximize the potential benefits of crowdfunding by various promoters. The conclusions will point to further directions of research, useful to improve the understanding of crowdfunding by deepening the analysis of relevant but less investigated aspects.